Synthesis and Antimicrobial Activity of Some Phenophosphazines - Lokhandwala, Snehal; Desai, K.R. (Asian Journal of Chemistry, 2012)
A new family of organophosphorus compounds namely 3-chloro-1-(10-hydroxy-10-oxo-5,10-dihydro-phenophosphazin-2-yl)-4-(substituted phenyl)-azetidin-2-one (3a-j) has been synthesized by reaction of 2-[(substituted benzylidene)-amino]-10-oxo-5,10-dihydro-phenophosphazin-10-ol (2a-j) with chloro acetyl chloride and triethyl amine. All these compounds were characterized by elemental and spectral analysis. Their antimicrobial activity was also evaluated.